Adverse Cardiovascular Effects of Phenylephrine Eye Drops Combined With Intravenous Atropine - Li, Qingyu; Pang, Jianxin; Deng, Yang; Zhang, Shaochong; Wang, Yong; Gao, Yang; Yuan, Xiaoyong; Wei, Yantao; Zhang, Hongbin; Tan, Junlian; Chi, Wei; Guo, Wenjun (Frontiers in Pharmacology, 2021)
Background Phenylephrine and atropine can cause serious adverse effects, when applied in combination. We investigated the effect of phenylephrine eye drops combined with intravenous atropine on the cardiovascular system in patients under general anaesthesia undergoing intraocular surgery. Methods Thirteen patients undergoing intraocular surgery under general anaesthesia were observed in this study; all were injected intravenously with atropine due to the oculocardiac reflex during surgery. Sixty-six SD rats that received phenylephrine eye drops and intravenous atropine treatment under general anaesthesia were assessed, of which 12 treated with these drugs simultaneously were administered normal saline or neostigmine. Blood pressure and heart rate were recorded and analysed. Findings The age of the patients ranged from seven to 14 years old with an average age of 10.7 years old, and 11 patients were male. In patients, 5% phenylephrine eye drops combined with intravenous atropine led to a significant heart rate increase; the increase lasted 20 minutes. The significant increase in diastolic blood pressure and systolic blood pressure lasted 15 and 25 minutes, respectively. From five to 25 minutes after intravenous atropine treatment, systolic blood pressure and diastolic blood pressure were both more than 20% higher than that at baseline. In rats, the blood pressure and heart rate changes were independent of the phenylephrine and atropine administration sequence but were related to the administration time interval. The neostigmine group showed a significant decrease in blood pressure after the increase from the administration of phenylephrine and atropine. Interpretation Phenylephrine eye drops combined with intravenous atropine have obvious cardiovascular effects, which can be reversed by neostigmine. These drugs combination should be used carefully for ophthalmic surgery, especially in patients with cardiocerebrovascular diseases.